Hubungan Faktor Risiko Komorbid Dengan Tingkat Kematian Pasien Covid-19 Di Puskesmas Manduro Kabupaten Mojokerto Bulan Januari – Juni Tahun 2021 - M Saputra; Putu Hade Wida Dewi; Ezia Nisa Febriyanti; Petronela C. J. Ribeiro; Putu Ayu Harpendani; Ayu Cahyani Noviana (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Patients who are confirmed positive for COVID-19 with comorbid or congenital diseases are a vulnerable group because they have a higher risk of mortality compared to others. The Head of the East Java Health Office explained that basedon the analysis in East Java Province, 95% of positive COVID-19 patients died due to comorbid diseases. The purpose ofthis study was to determine whether there was a relationship between comorbid risk factors and the mortality rate of Covid-19 patients at the Manduro Health Center, Mojokerto Regency in January-June 2021. This study was an observational study with a crosssectional approach. The population of this study was 135 people with a sample size was 97 people were taken by simple random sampling. The independent variable is a comorbid disease while the dependent variable is the death rate of Covid-19 patients. The results showed that there was a relationship between comorbid risk factors and the mortality rate of Covid-19 patients with a sig value of 0.000 (<0.05), the coefficient test value was C = 0.502. From the results of this study, it can be concluded that comorbid diseases increase the mortality risk of Covid-19 patients at the Manduro Health Center, Mojokerto Regency.